Evolution of epitaxial InAs nanowires on GaAs 111B. - Zhang, X; Zou, J; Paladugu, M; Guo, Y; Wang, Y; Kim, Y; Joyce, H; Gao, Q; Tan, H; Jagadish, C (2009)
A systematic investigation of the Au catalyst-assisted growth of epitaxial InAs nanowires (NW) on GaAs substrates was presented. Scanning electron microscopy (SEM) images of InAs NWs with different growth times show no vertical NWs in the sample with 1 min growth of InAs. High resolution transmission electron microscopy (HRTEM) investigations performed at the trace/substrate interface to determine the strain status show many misfit dislocations at the InAs/GaAs interface. The interfacial energy of InAs/Au is found to be higher than that of GaAs/Au, and these energetic considerations result in the Au catalysts retaining contact with GaAs. Vertical NWs initiate at trace intersections where the Au catalysts can not retain interfaces with the GaAs substrate. HRTEM image showing the junction between the base and InAs trace clearly present the epitaxially grown base on the InAs trace.